Review of the genus Amblymelanoplia Dombrow, 2002 (Coleoptera: Scarabaeidae: Melolonthinae: Hopliini) with the description of ninety-three new species from South Africa and observations on its biogeography and phylogeny - Dombrow, Holger E.; Colville, Jonathan F.; Bowie, Rauri C.k. (Zootaxa, 2022)
Twenty years after establishing the genus Amblymelanoplia Dombrow, 2002 a large amount of new material collected has warranted a critical review of the established species and a revision of the genus. From this process, we describe 93 new species from the Northern Cape, Western Cape, Mpumalanga and Limpopo Provinces of the Republic of South Africa. A lectotype is designated for Gouna burchelli Arrow, 1917 which is transferred to Amblymelanoplia. The new species are: A. aequabilis Dombrow, new species, A. albolineata Dombrow, new species, A. albosquamosa Dombrow, new species, A. alluaudi Dombrow, new species, A. aquifolia Dombrow, new species, A. arrowi Dombrow, new species, A. atritica Dombrow, new species, A. baehri Dombrow, new species, A. balkei Dombrow, new species, A. bicostata Dombrow, new species, A. bidentata Dombrow, new species, A. bimucronata Dombrow, new species, A. brancuccii Dombrow, new species, A. braunsi Dombrow, new species, A. brinckmanni Dombrow, new species, A. burmeisteri Dombrow, new species, A. caliginosa Dombrow, new species, A. carinata Dombrow, new species, A. castanea Dombrow, new species, A. cederbergensis Dombrow, new species, A. citrusdalensis Dombrow, new species, A. constricta Dombrow, new species, A. costata Dombrow, new species, A. crenata Dombrow, new species, A. deyrollei Dombrow, new species, A. dregei Dombrow, new species, A. drumonti Dombrow, new species, A. elkeae Dombrow, new species, A. enodisuturalis Dombrow, new species, A. fabricii Dombrow, new species, A. felschei Dombrow, new species, A. frischi Dombrow, new species, A. fryi Dombrow, new species, A. fusca Dombrow, new species, A. gifbergensis Dombrow, new species, A. glenlyonensis Dombrow, new species, A. goodhopensis Dombrow, new species, A. gydoensis Dombrow, new species, A. jekeli Dombrow, new species, A. klassi Dombrow, new species, A. kraatzi Dombrow, new species, A. kulzeri Dombrow, new species, A. laingsburgensis Dombrow, new species, A. lichtensteini Dombrow, new species, A. lajoyei Dombrow, new species, A. macrodentata Dombrow, new species, A. mamreensis Dombrow, new species, A. mcleodi Dombrow, new species, A. microdentata Dombrow, new species, A. montana Dombrow, new species, A. mortoni Dombrow, new species, A. multidentata Dombrow, new species, A. murrayi Dombrow, new species, A. nigra Dombrow, new species, A. obscura Dombrow, new species, A. paraunidentata Dombrow, new species, A. pascoei Dombrow, new species, A. pentheri Dombrow, new species, A. pseudocostata Dombrow, new species, A. pseudostrigata Dombrow, new species, A. pseudounidentata Dombrow, new species, A. pulchra Dombrow, new species, A. pulleiacea Dombrow, new species, A. punctata Dombrow, new species, A. pygidialis Dombrow, new species, A. reichei Dombrow, new species, A. robertsi Dombrow, new species, A. sainvali Dombrow, new species, A. scheini Dombrow, new species, A. scutellaris Dombrow, new species, A. selbi Dombrow, new species, A. septentrionalestris Dombrow, new species, A. setosa Dombrow, new species, A. soetwaterensis Dombrow, new species, A. sprecherae Dombrow, new species, A. squamosa Dombrow, new species, A. stalsi Dombrow, new species, A. stellenboschensis Dombrow, new species, A. strigata Dombrow, new species, A. sulcata Dombrow, new species, A. swartbergensis Dombrow, new species, A. swellendamensis Dombrow, new species, A. thomsoni Dombrow, new species, A. tradouwensis Dombrow, new species, A. tuberculata Dombrow, new species, A. turneri Dombrow, new species, A. unidentata Dombrow, new species, A. vansoni Dombrow, new species, A. webbi Dombrow, new species, A. wittmeri Dombrow, new species, A. worcesterensis Dombrow, new species, A. zuercherae Dombrow, new species and A. zumpti Dombrow, new species. Three cryptic species complexes within the species A. burchelli (Arrow, 1917) [+6], A. cornuta Dombrow, 2002 [+10] and A. capensis Dombrow, 2002 [+14] were detected. A revised key of the genus and observations about its biogeography and phylogeny are given. Important details of the morphological characters of the body and the parameres of the species are illustrated and their distributions are mapped. We also provide habitat information.